The sixth side of the Pentagon - Marker, Chris; Reichenbach, François 1921-1993 (First Run/Icarus Films, 2008)
The sixth side of the Pentagon is a first-person documentary on the October 1967 March on the Pentagon for the mobilization to end the war in Vietnam, with Marker filming in the midst of the often violent protest. It is a remarkable time capsule and a reminder of an historic turning point in the opposition to a long and unpopular war. [amazon]
Bildformat 1.33:1
Orig: Frankreich 1967
Enth. "The embassy"
Keywords: USA -- Department of Defense; Geschichte 1967; Jugendprotest; Vietnamkrieg; Demonstration; Washington, DC; DVD-Video